SUBJECT-VERB AGREEMENT ERRORS MADE BY SIXTH SEMESTER ENGLISH EDUCATION STUDENTS - Eki Putra Hidayatullah; Syarial . .; Gita Mutiara Hati (Universitas Bengkulu, 2017)
This resarch used descriptive quantitative method. This research aimed to find out subject- verb agreement errors made by sixth semester Engllish Education students of Universitas Bengkulu and to find out the possible causes of the errors. The samples of this research were sixth semester English Education students of Universitas Bengkulu in 2016/2017 academic year. The data were collected by conducting writing. The results of the data were analyzed descriptively by using Surface Strategy Taxonomy by Dulay et al (1982) to analyze the types of errors and theory of causes of errors by Richards (1974) to analyze the causes of errors. The result shows that there were 3 types of subject-verb agreement errors found in students’ essays. The errors were omission (49 %), addition (25 %) and misinformation (26 %). Another result shows that there were 2 possible causes of subject-verb agreement errors in this research. They were interlingual errors (2 %) and intralingual & developmental errors (98 %).